1997
DOI: 10.1002/(sici)1097-0215(19970207)70:4<390::aid-ijc3>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the Ki‐ras, p53 and APC genes in adenocarcinomas of the human small intestine

Abstract: In contrast to the origins of colorectal carcinomas, the mechanisms of carcinogenesis in the small intestine remain unclear. We therefore analyzed the mutational status of the Ki-ras, p53, and adenomatous polyposis coli (APC) genes in primary carcinomas of the small intestine and compared the mutation patterns with those established for colorectal cancers. DNA was extracted from 15 formalin-fixed, paraffinembedded lesions. Codons 12, 13 and 61 of the Ki-ras gene, exons 5-8 of the p53 gene, and codons 1268-1569… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
40
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 13 publications
2
40
1
Order By: Relevance
“…Although a few previous studies of small intestinal adenocarcinomas have examined KRAS and/or BRAF mutations, which are well-known oncogenes in colorectal cancer, most of these analyses were performed on small numbers of patients (Table 9). 1,3,[10][11][12][13][14][15][16][17][18][19][20] The frequency of KRAS mutations among small intestinal adenocarcinomas ranged from 9 to 83% in the previous studies. Previous studies from Japan with homogeneous ethnic groups showed a wide range of frequencies of KRAS mutation (9-71%), [13][14][15]19 and other studies with heterogeneous ethnic groups, such as studies from USA, also reported various frequencies of KRAS mutation (14-83%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a few previous studies of small intestinal adenocarcinomas have examined KRAS and/or BRAF mutations, which are well-known oncogenes in colorectal cancer, most of these analyses were performed on small numbers of patients (Table 9). 1,3,[10][11][12][13][14][15][16][17][18][19][20] The frequency of KRAS mutations among small intestinal adenocarcinomas ranged from 9 to 83% in the previous studies. Previous studies from Japan with homogeneous ethnic groups showed a wide range of frequencies of KRAS mutation (9-71%), [13][14][15]19 and other studies with heterogeneous ethnic groups, such as studies from USA, also reported various frequencies of KRAS mutation (14-83%).…”
Section: Discussionmentioning
confidence: 99%
“…1,3,[10][11][12][13][14][15][16][17][18][19][20] In addition, because most of these few analyses were performed on only small numbers of small intestinal adenocarcinoma patients, they need to be validated.…”
mentioning
confidence: 99%
“…In the study by Rashid and Hamilton, 15 allelic loss at chromosome 5q, the region of the adenomatous polyposis coli gene, was found to be extremely rare, detected in only one of 21 small intestinal adenocarcinomas (5%). Arai et al 16 and Bläker et al 17 demonstrated mutations in the adenomatous polyposis coli gene in 3 of a total of 36 small intestinal adenocarcinomas (8%) they examined. Furthermore, Wheeler et al 18 did not find any mutation in 21 cases.…”
Section: Discussionmentioning
confidence: 99%
“…30 Similar to that occurring in the adenoma-carcinoma sequence of colorectal tumorigenesis, 31,32 p53 mutation has been proposed as a late event during the development of small intestinal adenocarcinoma, which may serve a role in tumor progression. 15,33 The reported frequency of p53 mutation in small intestinal adenocarcinoma ranges from 0 to 43% by DNA-based analysis, 15,16,34,35 and 24 to 65% by immunohistochemistry. 15,18,23,33,36 Our data are in line with these observations and further demonstrate that in both small intestinal and colorectal adenocarcinomas, p53 overexpression, an indirect indication of p53 gene mutation, occurs only rarely in microsatellite instable tumors.…”
mentioning
confidence: 99%
“…[2][3][4] Recent studies, however, provide evidence for a somewhat different molecular pathogenesis of the majority of sporadic carcinomas in both locations. [5][6][7][8][9] Microsatellite and chromosomal instability (MSI and CIN) are two divergent types of genomic instability found in adenocarcinomas throughout the gastrointestinal tract, including the small intestine. 6,7,[9][10][11][12] MSI is caused by inactivation of the DNA mismatch repair system that may either result from promoter hypermethylation of the DNA mismatch repair gene MLH1 in sporadic carcinogenesis, 13 or following germline mutations in DNA mismatch repair system genes in hereditary nonpolyposis colorectal cancer.…”
mentioning
confidence: 99%